Evaluasi Program Makmur Pupuk Indonesia dalam Meningkatkan Ekosistem Usaha Perkebunan Sawit Rakyat Menggunakan Kriteria OECD-DAC: Studi Kasus di Provinsi Riau - Nasution, Zulfi Prima Sani (Inovasi, 2024)
The main challenge in the oil palm sub-sector, especially in smallholder oil palm plantations, is increasing productivity. Low productivity accompanied by fluctuations in input prices and commodity selling prices have a significant impact on the instability of farmers' income. To increase the productivity of smallholder oil palm, PT Pupuk Indonesia Holding Company (PIHC) initiated the Makmur Program. This program aims to overcome various challenges faced by smallholder farmers, including limited access to fertilizers, fluctuating fertilizer prices, and financial constraints that hinder the implementation of Good Agricultural Practices (GAP). The purpose of this study is to evaluate the success rate of the Makmur Program, starting from the business process, the partnership ecosystem, the role of each party. The research will assess the relevance, efficiency, effectiveness, impact, and sustainability of the program through quantitative and qualitative approaches based on the project and program evaluation guidelines published by the Organization for Economic Cooperation and Development - Development Assistant Committee (OECD-DAC 2021). The research focuses on three cooperatives in Riau Province, Indonesia, which were purposively selected due to the region's significant involvement in oil palm cultivation. The three cooperatives are Mojopahit Jaya Cooperative, Karya Sawit Cooperative, and Hasrat Jaya Cooperative. The Makmur program has facilitated access to quality fertilizer and encouraged collaboration between stakeholders. However, there are challenges to overcome, particularly in raising farmers' awareness, improving the efficiency of the program, and ensuring its long-term impact and sustainability. The Makmur Program in Riau's smallholder oil palm crop as a whole across the three cooperatives is categorized as “Partially Successful”. Keywords: Sustainability, smallholders, oil palm, productivity, fertilizer, Program Makmur